THE INFLUENCE OF GENERAL ATTITUDES, SUBJECTIVE NORMS, AND CONTROL BELIEFS ON THE INTENTION TO SUSTAINABLY USE ARTIFICIAL INTELLIGENCE IN THE INDONESIAN FINANCIAL SERVICES INDUSTRY - Ivana Santoso, Margaretha; Dwi Hastuti, Theresia (AKUNTANSI DEWANTARA, 2024)
The research objective is to analyze how general attitude, subjective norms, and perceived control influence the intention to use artificial intelligence (AI) sustainably among financial service industry workers in Indonesia. This quantitative research utilized a survey method with a Likert scale questionnaire, involving 138 respondents from the Indonesian financial service industry. Data analysis was conducted using SPSS to perform validity, reliability, and multiple regression tests. The results indicate that both general attitude and subjective norms positively influence the intention to use AI sustainably. However, perceived control does not have a significant positive effect on the intention to use AI sustainably. These findings suggest that the perception of AI's usefulness and social encouragement significantly impact sustainable usage intentions, whereas individual confidence in AI usage does not. The study supports the Theory of Planned Behavior by confirming the roles of attitude and subjective norms in technology adoption intentions. Practically, the findings provide insights for companies and policymakers to focus on enhancing positive perceptions and social support for AI adoption to ensure its sustainable use. This research uniquely addresses the intention to use AI sustainably within the Indonesian financial services sector, providing specific insights into the factors influencing AI adoption in this context